Evaluation of the in vitro efficacy of selected plant extracts against strawberry anthracnose disease in highlands of Sri Lanka - Kalupahana Pushpanjie; Arulappu George Chandra Babu; Karuna Pedige Harsha Chathuranga; Herath Kumara Bandarage Muditha Indrajith Karunarathna (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2026)
Anthracnose was one of the major diseases of strawberry cultivation in Sri Lanka, caused by a fungal pathogen Colletotrichum acutatum Simmonds, and the application of synthetic fungicides was the well-known method used in disease management. Since there was a requirement to find alternative methods to control the disease, six plant extracts were tested as an organic management approach. The study aimed to evaluate the in vitro efficacy of selected plant extracts against Colletotrichum acutatum isolated from strawberry and to identify promising botanical alternatives to synthetic fungicides for sustainable strawberry cultivation in the highlands of Sri Lanka. In well diffusion test, sterilized distilled water, garlic (0.25 g/mL), Mint (0.25 g/mL), rosemary (0.25 g/mL), turmeric (0.25 g/mL), ginger (0.25 g/mL), cinnamon oil (0.25 mL/mL), Fungicide (Chlorothalonil 500 g/L SC (0.003 mL/mL) were the tested treatments. Cinnamon oil suspension (0.25 g/mL) and garlic bulb extract (0.25 g/mL) were able to control C. acutatum under in vitro conditions. However, according to the sensory evaluation test of plant extracts treated fruits, the most preferable plant extract application was garlic bulb extract, which is having significantly similar “overall acceptance” with untreated fresh strawberry fruits. Based on the results, garlic bulb extract is suggested as an organic disease management method which can be used in an anthracnose management method in organic strawberry production.